Human Umbilical Mesenchymal Stem Cells Display Therapeutic Potential in Rheumatoid Arthritis by Regulating Interactions Between Immunity and Gut Microbiota via the Aryl Hydrocarbon Receptor - Li, Xiaoya (Front Cell Dev Biol, 2020)
BACKGROUND: Rheumatoid arthritis (RA) is an autoimmune disease that may be associated with gut microbiota via the aryl hydrocarbon receptor (AhR). Human umbilical mesenchymal stem cells (HUMSCs) have therapeutic potential against RA, but the underlying mechanism has not been fully elucidated. The purpose of this study was to explore the mechanism of action of HUMSCs in rats with collagen-induced arthritis (CIA). METHOD: HUMSCs (1 × 10(6)) were transplanted into each rat with CIA. The tissue localization of HUMSCs and the therapeutic effects in the ankles were assessed. The immune status and expression of immune-related genes and proteins in related lymphoid tissues were subsequently tested. Furthermore, the levels of immune-related factors in serum and the changes in gut microbiota in the ileum were detected, and the levels of indole and their derivatives in plasma and the levels of AhR in the ileum were evaluated. RESULTS: HUMSCs homed to the popliteal lymph node (PLN), mesenteric lymph node (MLN), ankle cartilage, and ileum mucosa in rats with CIA. The transplantation of HUMSCs reduced the pathology scores and the degree of bone damage in the ankles. The immune status of T regulatory cells (Tregs) and T helper (Th)17 cells and the gene expression levels of interleukin (IL)-10, transforming growth factor (TGF)-β1, and IL-17A were altered in the PLN, which is the lymph tissue closest to the nidus, and the MLN, which is one of the gut-associated lymphoid tissues (GALTs). The proportion and function of B cells, Tregs, and Th17 cells were regulated in other GALTs, namely, Peyer’s patches and the lamina propria. The gene expression of TGF-β1 and IL-17A and protein expression of IL-10, TGF-β1, IL-17A, IL-22, and immunoglobulin A (IgA) were modulated in the ileum, and the serum levels of IL-10, TGF-β1, IL-17A, IL-1β, and tumor necrosis factor (TNF)-α were regulated in the rats with CIA. The relative abundances of the genera Bacteroides and Bacillus were increased in the HUMSCs-treated rat with CIA; in addition, the levels of indole, indoleacetic acid, and indole-3-lactic acid were consistently upregulated, and this upregulation was accompanied by increases in AhR gene and protein expression. CONCLUSION: Our study demonstrates that HUMSCs play a therapeutic role in rats with CIA by regulating the interactions between host immunity and gut microbiota via the AhR.